DAKWAH BAHASA LOKAL PADA MASYARAKAT KECAMATAN BONTONOMPO SELATAN KABUPATEN GOWA - Herman, Herman (Jurnal Dakwah Tabligh, 2020)
The aim of this research is to know the use of Makassar Language in Dakwah activity at South Bontonompo district, Gowa regency. The problem of this research involves the community understanding about Dakwah through Makassar language at South Bontonompo district Gowa regency; the implementation of in Dakwah through Makassar language at South Bontonompo district Gowa regency. This research used qualitative descriptive research with Normative and Dakwah approach. The researcher gets the data from community, Dai, public figure of South Bontonompo district Gowa regency. The method of collecting data are observation, interview, documentation, and literature review. Data processing and analysis techniques are carried out through three stages namely data reduction, data presentation and conclusion making. The results of this study indicate that: 1) Community understanding of the Makassar language Dakwah in South Bontonompo district of Gowa Regency, namely: a) Da'wah is easier to understand, b) Da'wah is more touching, c) Da'wah is closer (emotional connection), d) Dakwah has meaning deeper; 2) The implementation of the Makassar language in da'wah in South Bontonompo District, Gowa Regency, namely: a). Makassar Sinrili, b). Makassar Kelong, c). Paruntu 'Kana Makassar, d). Pasang Makassar, as well as Khotbah and Lectures.